THE INFLUENCE OF PROBLEM BASED LEARNING (PBL) MODEL ON IMPROVING LEARNING OUTCOMES IN SCIENCE SUBJECTS IN GRADE IV OF SD NURUL HUDA II YAPIS - Ernawati, Ernawati; Mutmainnah, Nurul; Neti S, Neti S; Bariyyah, Sitti Khairul; Dewi, Azizah Kusuma (Indonesian Journal of Educational Development (IJED), 2024)
This study aims to determine whether the Problem Based Learning (PBL) model influences the improvement of learning outcomes in Science subjects in Grade IV of SD Nurul Huda II Yapis for the academic year 2023/2024. The results of this research are expected to be beneficial both theoretically and practically. This study is an experimental research with a quasi-experimental design. Data collection techniques include observation, documentation, and testing. The data analysis technique used is the Independent Samples T test to determine if there is an effect of using the Problem Based Learning model on improving student learning outcomes. Based on the research results, the average scores obtained in the experimental class were 75.96 and in the control class were 65.08, as evidenced by the students' post-test results. The hypothesis testing resulted in a calculated t-value > critical t-value, specifically 2.596 > 1.673, with a significance level less than 0.05 (0.012). This indicates that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, it can be concluded that there is a positive and significant influence of using the Problem Based Learning model on improving learning outcomes in Grade IV of SD Nurul Huda II Yapis for the academic year 2023/2024.